Variation of stemness markers expression in tumor nodules from synchronous multi-focal hepatocellular carcinoma - an immunohistochemical study - Regina Cheuk-lam Lo; Carmen Oi-ning Leung; Kenneth Siu-ho Chok; Irene Oi-lin Ng (BMC, 2017)
Abstract Background Advancing knowledge in molecular pathogenesis of hepatocellular carcinoma (HCC) opens up new horizons in the diagnostic, prognostic and therapeutic perspectives. Assessing the expression of molecular targets prior to definitive treatment is gaining importance in clinical practice. In this study, we investigated the variation in expression pattern of stemness markers in synchronous multi-focal HCC. Methods In the first cohort, 21 liver explants with multi-focal HCC were examined for expression of stemness markers EpCAM, Sox9 and CK19 by immunohistochemistry (IHC). Expression data of 50 tumor nodules were analyzed to determine the concordance of expression among nodules in the same livers. In the second cohort, 14 tumor nodules from 6 multi-focal HCC cases proven as intra-hepatic metastasis were examined for Soc9 immunoexpression. Results In the first cohort, thirty nodules from 16 cases expressed one or more markers, with Sox9 being most frequently expressed. Complete concordance of expression pattern for all 3 markers was observed in 6 cases. Discrepancy of staining degree was noted in 4 cases for EpCAM, 14 cases for Sox9, and 6 cases for CK19. A two-tier or three-tier difference in staining scores was noted in 5 cases for Sox9 and one case for CK19. With Sox9, identical tumor morphology in terms of Edmondson grading and growth pattern did not infer the same degree of immunoexpression; and the largest tumor nodule was not representative of highest IHC score. In the second cohort of intra-hepatic metastasis, complete concordance of Sox9 expression level was observed in 5 out of 6 cases; while the remaining case showed a 1-tier difference of positive staining. Conclusions Our findings suggested that clonality of tumor nodules is apparently an important factor to infer immunoexpression pattern. When there is limited information to discern multiple primaries versus intra-hepatic metastasis in multi-focal HCC, discordant degree of stemness markers expression among tumor nodules was commonly observed especially for markers with higher frequency of expression. Pathological features alone do not necessarily indicate the expression pattern of the synchronous nodule and in this scenario examination of each tumor nodule is justified.